Central African Republic : Sixth Review Under the Extended Credit Facility Arrangement, Requests for Waivers of Nonobservance of Performance Criteria and Financing Assurances Review-Press Release; Staff Report; and Statement by the Executive Director for the Central African Republic. (IMF Staff Country Reports; Country Report ;, 2019)
President Touadera signed a new peace agreement on February 6, 2019 with 14 armed groups. This agreement calls for the establishment of an inclusive government, the deployment of joint brigades, an acceleration of decentralization efforts, and the co-management of natural resources. While its implementation has started, including with the appointment of more inclusive government, the security situation remains volatile. The World Bank (WB) and the European Union (EU) have substantially increased their budgetary support (grants) for 2019-20. The authorities have expressed a strong interest in a successor arrangement.